2023
DOI: 10.1101/2023.01.13.523596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The junctional mechanosensor AmotL2 regulates YAP promotor accessibility

Abstract: Endothelial cells (ECs) are constantly exposed to mechanical forces in the form of fluid shear stress, extracellular stiffness, and cyclic strain. How these forces are sensed by ECs remains an understudied aspect in the homeostatic regulation of the circulatory system. Angiomotin-like 2 (AmotL2) is localised to EC junctions and is required for alignment and actin reorganisation under conditions of high shear stress. Here we show that AmotL2 crucially regulates transcription and promotor activity of the YAP gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…A follow-up preprint from our laboratory indicates that AmotL2 is required for lamin A expression and that AmotL2 loss reduces chromatin accessibility of the YAP promotor via increased repressive H3K27me3 marks to silence YAP transcription in ECs. This work also indicates that YAP/TAZ are required for the nuclear actin cap in ECs of the thoracic aorta ( Mannion et al, 2023 preprint), in agreement with Coleman et al (2020) showing that YAP/TAZ were required for EC alignment via their transcriptional activation of the GTPase activator gene ARHGAP18 and via modulation of actin dynamics ( Coleman et al, 2020 ). Interestingly, YAP also plays a central role in regulating the actin cap in epithelial cells by directly binding to the promotors of LMNB1 and ACTR2 ( Sladitschek-Martens et al, 2022 ).…”
Section: A Continuous Connection To the Nucleussupporting
confidence: 73%
See 1 more Smart Citation
“…A follow-up preprint from our laboratory indicates that AmotL2 is required for lamin A expression and that AmotL2 loss reduces chromatin accessibility of the YAP promotor via increased repressive H3K27me3 marks to silence YAP transcription in ECs. This work also indicates that YAP/TAZ are required for the nuclear actin cap in ECs of the thoracic aorta ( Mannion et al, 2023 preprint), in agreement with Coleman et al (2020) showing that YAP/TAZ were required for EC alignment via their transcriptional activation of the GTPase activator gene ARHGAP18 and via modulation of actin dynamics ( Coleman et al, 2020 ). Interestingly, YAP also plays a central role in regulating the actin cap in epithelial cells by directly binding to the promotors of LMNB1 and ACTR2 ( Sladitschek-Martens et al, 2022 ).…”
Section: A Continuous Connection To the Nucleussupporting
confidence: 73%
“…The onset of LF triggered the association of AmotL2, VE-cadherin and p120 catenin with the actin cytoskeleton, forming a contiguous pathway from cell-cell junctions to the nuclear membrane. Additionally, in vivo deletion of endothelial AmotL2 led to impaired EC alignment and nuclear morphology ( Zhang et al, 2023 ) and, as shown in recently preprinted work, impacts on chromatin accessibility ( Mannion et al, 2023 preprint). In a strikingly analogous role to AmotL2, neuropilin 1 was also shown to bind VE-cadherin in a flow-dependent manner, promote flow-induced association of p120 catenin and VE-cadherin, and regulate downstream anti-inflammatory signalling ( Bosseboeuf et al, 2023 ).…”
Section: Endothelial Mechanosensory Mechanismsmentioning
confidence: 82%